WATER MANAGEMENT IN TIDAL SWAMPY AREAS FOR COCONUT CULTIVATION - Edy Sigit Sutarta (International Coconut Community, 1990)
Coconut has been traditionally cultivated in tidal swampy areas by farmers for a long time. Coconut growth in this area needs a good water management system, besides fertilization. Flooding in this area not only retards coconut growth, but also reduces production. A water management system, mainly‑drainage has been used by farmers depending on conditions of the area and farmer's abilities. Functions and types of water management system that have been used for coconut cultivation in tidal swampy areas are discussed.